Stimulasi Motorik Halus pada Anak Usia Dini pada Kegiatan Meronce di KB Seroja - Khairun Nisa; Ridho Arifia Pratama Silangit; Arifah Husni Fadillah; Rabiatul Adawiyah Lubis; Rini Wahyuni Siregar (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The pith of this investigation is to figure out the groundwork for the delight of learning in chipping away at kids' fine planned developments through play practice at the Seroja KB Playing Social occasion, youngsters' responses to this learning in dealing with youngsters' fine organized developments through play practice at the Seroja KB Playing Get-together. KB Seroja play bunch, the challenges looked by teens in doing errands in this learning are to additionally foster the fine organized developments of teens since kids are less powerful in moving their fingers with the goal that youngsters experience issues in working and the hardships saw by teachers during ronce figuring out how to prepare kids' fine, planned developments through ronce practices in play bunches at KBSeroja.